Real-world safety of carboplatin in non-small cell lung cancer: a retrospective signal detection and subgroup analysis based on the FAERS database - Wang, Lei; Yang, Kunpeng; Zhao, Hui; Lv, Peiyun; Cai, Chenglun; Wang, Zhe; Wang, Bao (Frontiers in Medicine, 2025)
IntroductionCarboplatin is frequently employed in the treatment of non-small cell lung cancer (NSCLC), yet the real-world safety profile—including underrecognized adverse events (AEs) and subgroup-specific risk variations—remains incompletely understood. This study aims to systematically assess carboplatin-related AEs and explore demographic factors that may influence risk.MethodsA retrospective analysis was performed using data from the FDA Adverse Event Reporting System (FAERS) spanning the first quarter of 2004 to the third quarter of 2024. Standardized terminology harmonization and multiple disproportionality methods—including reporting odds ratio (ROR), proportional reporting ratio (PRR), and Bayesian analysis—were applied to detect potential safety signals. Subgroup analyses were conducted to identify sex- and age-specific variations in risk.ResultsAmong 4,748 reports meeting inclusion criteria, known hematologic toxicities (e.g., anemia, neutropenia) and renal impairment were confirmed. Additionally, previously unlabeled risks emerged, such as abdominal pain (higher incidence in females), neutropenic sepsis (predominant in males and older adults), and hypothyroidism. Subgroup analyses revealed distinct patterns: males exhibited increased infection-related events, whereas females were more prone to gastrointestinal and hepatic complications. Patients aged ≥65 years showed increased multisystem involvement, particularly affecting hematologic and renal functions.DiscussionThese findings underscore the necessity of tailored monitoring strategies for carboplatin, taking into account patient sex and age, especially when used in conjunction with immunotherapy. The study’s insights support refining pharmacovigilance strategies and updating clinical guidelines to enable early intervention and improve personalized management for patients with NSCLC.